Effects of pumpkin seed extract on growth, blood biochemistry, antioxidant status, immunity, and digestive enzymes of common carp (Cyprinus carpio L.) fingerlings - Tayfun Karatas; Teoman Ozgur Sokmen; Sultan Tuna Akgol Gur (Aquaculture Reports)
Pumpkin seeds possess antioxidant, anthelmintic, cytoprotective, antidepressant, antidiabetic, and antitumor properties. This study aimed to evaluate the effects of pumpkin seed extract (PSE) on the growth performance, blood biochemistry, oxidative stress, antioxidant status, immunity, and digestive enzyme activity in common carp (Cyprinus carpio). Eighty carp fingerlings (average weight: ∼13 g) were distributed into aquaria (80 × 29 × 42 cm; water volume: 100 L) with 20 fish per aquarium. The experimental design included one control group (0 % PSE) and three treatment groups supplemented with 1 %, 2 %, or 4 % PSE, each with three replicates. The fish were fed their respective diets for 70 days. The inclusion of 1 %, 2 %, and 4 % PSE significantly influenced all measured parameters. The specific growth rate (SGR), weight gain (WG), and feed conversion ratio (FCR) improved with increasing dietary PSE levels. Compared to the control group, PSE supplementation at all doses markedly elevated biomarkers, such as total protein, trypsin, amylase, lipase, superoxide dismutase (SOD), catalase (CAT), lysozyme, total immunoglobulin (IG), and white blood cell (WBC) counts. On the other hand, significant reductions were observed in glucose, aspartate aminotransferase (AST), alanine aminotransferase (ALT), total cholesterol, triglycerides, and malondialdehyde (MDA) levels. The 4 % PSE treatment exhibited the most pronounced effects across all parameters. In sum, dietary supplementation with 4 % PSE effectively enhanced stress resilience, growth performance, immune response, antioxidant capacity, and digestive enzyme activity in common carp fingerlings compared to lower PSE concentrations and the untreated control group.